"Keeping Control": A user‐led exploratory study of mental health service user experiences of targeted violence and abuse in the context of adult safeguarding in England. (30th June 2019) - Carr, Sarah; Hafford‐Letchfield, Trish; Faulkner, Alison; Megele, Claudia; Gould, Dorothy; Khisa, Christine; Cohen, Rachel; Holley, Jessica
Abstract: The situation for people with mental health problems as a group of disabled people who experience targeted violence and abuse is a complex one. Disabled people, particularly those with mental health problems, are at higher risk of targeted violence and hostility with few effective evidence‐based prevention and protection strategies. Achieving effective safeguarding for adults with mental health problems is characterised by differential attitudes to and understandings of abuse by safeguarding practitioners, as well as systemic issues arising from multi‐agency working. "Keeping Control" was a 16‐month user‐led, co‐produced exploratory qualitative study into service user experiences of targeted violence and abuse that was examined in the context of Care Act 2014 adult safeguarding reforms in England. User‐controlled interviews of mental health service users ( N = 23) explored their experiences and concepts of targeted violence and abuse, prevention and protection. Preliminary findings from these interviews were discussed in adult safeguarding and mental health stakeholder and practitioner focus groups ( N = 46). The data were also discussed via two facilitated Twitter chats (responses N = 585 and N = 139). Mental health service users' experiences and concepts of risk from others, vulnerability and neglect can be different to those of practitioners but should be central to adult safeguarding. Histories of trauma, multi‐factorial abuse; living with fear and stigma as well as mental distress; the effects of "psychiatric disqualification" and individual blaming should be addressed in adult safeguarding in mental health. Fragmented responses from services can mean a person becomes "lost in the process". Staff can feel disempowered, afraid or lacking in confidence to "speak up" for individuals in complex service systems with poor communication and lines of accountability. Adult safeguarding practitioners and stakeholders need to be confident, accessible and respond quickly to service users reporting incidents of targeted violence and abuse particularly in closed environments such as wards or supported housing.